Shifting Ethnic Identities in Spain and Gaul, 500-700 : From Romans to Goths and Franks - Buchberger, Erica, 1979- (Book collections on Project MUSE., 2017)
Traditional scholarship on post-Roman western culture has tended to examine the ethnic identities of Goths, Franks, and similar groups while neglecting the Romans themselves, in part because modern scholars have viewed the concept of being Roman as one denoting primarily a cultural or legal affiliation. As this book demonstrates, however, early medieval 'Romanness' also encompassed a sense of belonging to an ethnic group, which allowed Romans in Iberia and Gaul to adopt Gothic or Frankish identities in a more nuanced manner than has been previously acknowledged in the literature.